Sundaland's east–west rain forest population structure: variable manifestations in four polytypic bird species examined using RAD‐Seq and plumage analyses. (28th May 2017) - Lim, Haw Chuan; Gawin, Dency F.; Shakya, Subir B.; Harvey, Michael G.; Rahman, Mustafa A.; Sheldon, Frederick H.
Abstract: Aim: A current model of rain forest population diversification in Sundaland specifies east–west vicariance into refugia during the early Pleistocene. In some taxa, this division was followed by dispersal and apparent secondary contact on Borneo in the late Pleistocene. To investigate genetic, morphological, spatial and temporal characteristics of the model, we compared genomic population and plumage variation among four bird species with east–west mtDNA and plumage structure. Location: Borneo and western Sundaland (Sumatra and the Malay Peninsula). Methods: We quantified plumage patterns among populations of two muscicapids ( Copsychus saularis and Kittacincla malabarica ) and two timaliids ( Mixornis gularis and Trichastoma malaccense ), and compared them with population genetic patterns determined from (1) SNPs produced by RAD‐Seq and (2) previously sequenced mtDNA. Results: All four species exhibit east–west variation in morphological and some genetic characters, but patterns are idiosyncratic. Copsychus saularis' mtDNA and plumage change gradually across Borneo, but RAD‐Seq comparisons indicate no population structure. In K. malabarica, all three characteristics change abruptly and concurrently on Borneo. In M. gularis, the main east–west break occurs between Borneo and western Sundaland, with marginal mtDNA, plumage and RAD‐Seq structure on Borneo. T. malaccense exhibits two distinct mtDNA and genomic transitions, an early Pleistocene break between western Sundaland and Borneo, and a Pliocene break between the north‐east and the rest of Borneo. Despite this deep genetic division, its plumage changes clinally across Borneo. Main conclusions: MtDNA, plumage and RAD‐Seq patterns may vary depending on such factors as pre‐Pleistocene distribution, habitat requirements and dispersal propensity, differential introgression among the three character types, selection on plumage and phylogenetic relationships.